RENEB accident simulation exercise. (2nd January 2017) - Brzozowska, Beata; Ainsbury, Elizabeth; Baert, Annelot; Beaton-Green, Lindsay; Barrios, Leonardo; Barquinero, Joan Francesc; Bassinet, Celine; Beinke, Christina; Benedek, Anett; Beukes, Philip; Bortolin, Emanuela; Buraczewska, Iwona; et al.
Abstract: Purpose: The RENEB accident exercise was carried out in order to train the RENEB participants in coordinating and managing potentially large data sets that would be generated in case of a major radiological event. Materials and methods: Each participant was offered the possibility to activate the network by sending an alerting email about a simulated radiation emergency. The same participant had to collect, compile and report capacity, triage categorization and exposure scenario results obtained from all other participants. The exercise was performed over 27 weeks and involved the network consisting of 28 institutes: 21 RENEB members, four candidates and three non-RENEB partners. Results: The duration of a single exercise never exceeded 10 days, while the response from the assisting laboratories never came later than within half a day. During each week of the exercise, around 4500 samples were reported by all service laboratories (SL) to be examined and 54 scenarios were coherently estimated by all laboratories (the standard deviation from the mean of all SL answers for a given scenario category and a set of data was not larger than 3 patient codes). Conclusions: Each participant received training in both the role of a reference laboratory (activating the network) and of a service laboratory (responding to an activation request). The procedures in the case of radiological event were successfully established and tested.